Geoprospectiva, herramienta para la formulación de un modelo de inteligencia territorial (soberanía alimentaria y el desarrollo sostenible): experiencia de construcción participativa en el resguardo indígena La Victoria de la Etnia Piapoco (2021)
The territory is the product of the constant interactions between those who inhabit the spaces based on their  perceptions, conceptions and experiences. This defines, to a great extent, the identity of the communities that signify, modify and administer it. Faced with these interactions, frustrations or possibilities can be found in the development of the communities and their quality of life. This article recognizes how, in the geoprospective exercise developed by the Piapoco indigenous community based on the participatory action research (PAR), the proposal of a territorial intelligence model is structured within the framework of sustainable development and food sovereignty at La Victoria indigenous reserve, Colombia. This proposal is carried out in response to the actual needs and worldview of the indigenous community, as support for decision making and the development of the action plan of their life plan.